2010
DOI: 10.1093/carcin/bgq147
|View full text |Cite
|
Sign up to set email alerts
|

The role of EZH2 and DNA methylation in the silencing of the tumour suppressor RUNX3 in colorectal cancer

Abstract: In gastric cancer, a new epigenetic mechanism of tumour suppressor loss has been suggested where the histone methyltransferase enhancer of zeste homolog 2 (EZH2) is responsible for loss of expression of RUNX3. This is consistent with EZH2 upregulation in multiple cancer types being associated with poor prognosis. We investigated whether EZH2 influences the expression of RUNX3 in colorectal cancer (CRC) and whether this is independent of methylation. We determined protein and messenger RNA (mRNA) levels of EZH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 27 publications
(38 reference statements)
6
49
1
5
Order By: Relevance
“…Our data also show that CSMD1 DNA methylation is significantly positively correlated with both methylated ALX4 and the known PRC2 target RUNX3. Observing RUNX3 methylation in our data coincides with others who have reported that 21% of colorectal cancer have RUNX3 hypermethylation [48]. We conclude that CSMD1 silencing by PRC2-mediated histone modifications may have impacted the somatic mutation landscape through acquired DNA methylation [49], [50].…”
Section: Resultssupporting
confidence: 89%
“…Our data also show that CSMD1 DNA methylation is significantly positively correlated with both methylated ALX4 and the known PRC2 target RUNX3. Observing RUNX3 methylation in our data coincides with others who have reported that 21% of colorectal cancer have RUNX3 hypermethylation [48]. We conclude that CSMD1 silencing by PRC2-mediated histone modifications may have impacted the somatic mutation landscape through acquired DNA methylation [49], [50].…”
Section: Resultssupporting
confidence: 89%
“…These results are consistent with a growth-promoting role for EZH2 in colon cancer and are in contrast to a recent report indicating that the growth of colon cancer cells is not affected by siRNA-mediated EZH2 depletion [22].…”
Section: Discussionsupporting
confidence: 90%
“…[28,29] EZH2 expression has also been linked by some investigators to RUNX3 expression in various cancer types. [3][4][5][6] However, our results suggest that EZH2 expression appears to be decoupled from RUNX3 downregulation. A majority of the DLBCL tumors in our study showed EZH2 expression, consistent with the literature.…”
Section: Discussioncontrasting
confidence: 50%
“…[2] In particular, EZH2 has been shown to mediate epigenetic silencing of RUNX3 in malignancies including gastric, breast, prostate, colon, pancreatic, [3] neuroblastoma, [4] and cholangiocarcinoma. [5] However, other studies failed to find an association between RUNX3 downregulation and EZH2 expression in colorectal carcinoma [6] suggesting alternative mechanisms may exist for RUNX3 loss. A few studies have explicitly investigated this possibility, and present evidence for RUNX3 downregulation due to loss of function point mutation, [7] copy number loss, [8] and aberrant cytoplasmic localization.…”
Section: Introductionmentioning
confidence: 99%